Visualização de estrutura de domínios em cerâmicas e nanoestruturas ferroelétricas via microscopia de piezoresposta - Gonçalves, André Marino (2013)
In this work, the domain structure of a transparent ferroelectric ceramic of (Pb0,79La0,21)TiO3 (PLT 21) was investigated in detail by piezoresponse force microscopu (PFM) and a protocol of measurements and analysis of the piezoresponse for the tridimensional reconstruction of the polarization in ferroelectric domains, including from mono and polycrystalline materials was developed. With this protocol, properties of domains and domain walls of the PLT 21 ceramic and of a PbTiO3 (PT) thin film were investigated. Three types of domains were recognized in the PLT 21 ceramic: domains separated by 180° walls, and domains separated by 90° walls in two scales, one in wich the domains have dimensions of about 1 μm and another with dimensions lower than 100 nm. Classical domain structures of lamellae and herringbones, and even more exotic structures as quadrants could be observed in PLT 21. This last one might suggest the existence of flux closure states of polarization in ferroelectric ceramics. In our knowledge this is the first time that quadrant structures are observed in ceramics. We could also observe in PLT 21 ceramic, ferroelectric domains that run through de grain boundary. Analysis of the reorientation of polarization by applying a localized BIAS field, revealed a strong electromechanical coupling in the sample, with the appearance of new 90° domain structure as a way to compensate local deformations generated by the poling process. The domain structure of the PT thin film revealed grains with monodomain structure and grains with polydomain structure, being the latter preferentially formed by 90° walls. The study of the reorientation of domains in the thin films of PT, showed the formation of a monodomain structure in the majority of the grains after the poling process, what significantly differs from the results of the PLT 21 ceramics. Lastly, thin films of Pb(Fe0,5Nb0,5)O3 (PFN) with good structural, microstructural and electrical properties were produced by radio frequency sputtering (R.F. Sputtering) with different thickness (50 nm 950 nm). The values of remnant polarization and coercive field of the hysteresis loop were 7 μC/cm2 and 70 kV/cm, respectively, which are bigger than many results found in the literature. Ferroelectric local properties were investigated in monolithic thin films (i.e., films that have a single grain in the thickness) of PFN and compared with the properties obtained in polycrystalline thin films of PT.